2016
DOI: 10.1159/000442616
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Regulates Tau Phosphorylation through Wnt Signaling Pathway in PC12 Cells

Abstract: Background/Aims: Leptin, an adipocytokine produced endogenously in the brain, is decreased in Alzheimer's disease(AD) and has also been shown to reduce Aβ levels in vitro and in vivo. Sets of evidence show that leptin reduces Aβ production and tau phosphorylation in neuronal cells and transgenic mice models of AD. Herein, we investigated the signaling pathway activated by leptin, to better understand its mechanism of action. Methods: Western blotting was performed to assess the levels of phosphor-tau and Bax, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Notably, we observed that clusters 1 and 3 were mainly enriched in the normal group, cluster 2 was remarkably clustered in HSIL, and clusters 6, 7, 9 and 13 were prominent in CC (Figure 2C). Moreover, by analysing the marker gene expression and functional pathways of these ‘HPV‐related clusters,’ we discovered that clusters 1 and 3 enriched in the normal cervix featured antineoplastic effects and highly expressed multiple tumour suppressors (SLC5A8, DERL3) (Figure 2D), thereby suppressing cell proliferative, migratory and invasive capacities 9,10 . On the other hand, cluster 2, representing HSIL, manifested high cellular motor capacity, specifically expressing genes related to cell adhesion (CDH16, CDH17 and VSIG1) 11,12 and extracellular matrix degradation (CTSE) (Figure 2E), thus potentially promoting the expansion of atypical cells in intraepithelial neoplasia progression.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, we observed that clusters 1 and 3 were mainly enriched in the normal group, cluster 2 was remarkably clustered in HSIL, and clusters 6, 7, 9 and 13 were prominent in CC (Figure 2C). Moreover, by analysing the marker gene expression and functional pathways of these ‘HPV‐related clusters,’ we discovered that clusters 1 and 3 enriched in the normal cervix featured antineoplastic effects and highly expressed multiple tumour suppressors (SLC5A8, DERL3) (Figure 2D), thereby suppressing cell proliferative, migratory and invasive capacities 9,10 . On the other hand, cluster 2, representing HSIL, manifested high cellular motor capacity, specifically expressing genes related to cell adhesion (CDH16, CDH17 and VSIG1) 11,12 and extracellular matrix degradation (CTSE) (Figure 2E), thus potentially promoting the expansion of atypical cells in intraepithelial neoplasia progression.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, by analysing the marker gene expression and functional pathways of these ‘HPV‐related clusters,’ we discovered that clusters 1 and 3 enriched in the normal cervix featured antineoplastic effects and highly expressed multiple tumour suppressors (SLC5A8, DERL3) (Figure 2D ), thereby suppressing cell proliferative, migratory and invasive capacities. 9 , 10 On the other hand, cluster 2, representing HSIL, manifested high cellular motor capacity, specifically expressing genes related to cell adhesion (CDH16, CDH17 and VSIG1) 11 , 12 and extracellular matrix degradation (CTSE) (Figure 2E ), thus potentially promoting the expansion of atypical cells in intraepithelial neoplasia progression. Additionally, we observed that clusters 6, 7, 9 and 13 (CASP14, PRSS27, CALML5) (Figure 2F ), which were enriched in CC, manifested high expression levels of genes related to carcinogenic pathways such as epithelial‐to‐mesenchymal transition, tumour cell proliferation, migration, invasion and angiogenesis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Leptin reduces the production of Aβ from amyloid precursor proteins by inhibiting the γ-secretase complex 10 and diminishes extracellular Aβ by driving Aβ uptake into cells 11 . Leptin inhibits the production of hyperphosphorylated tau that forms neurofibrillary tangles, which are the key pathological features of AD 11 , 12 . The correlation between plasma leptin levels and body fat is known to persist with age and appear in older adults 35 .…”
Section: Discussionmentioning
confidence: 99%
“…The exact underlying mechanisms are still unclear but one plausible explanation for this might be due to the fat-derived hormone leptin 6 . A previous study showed that higher plasma leptin levels were associated with a lower risk of AD 9 , suggesting leptin may play a role in reducing the production of amyloid beta (Aβ) 10 , diminishing extracellular Aβ 11 , and inhibiting the production of hyperphosphorylated tau which are the key pathological features of AD 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%